Confidential Care for Adolescents in the U.S. Health Care System - Priya R. Pathak; Adriana Chou (Journal of Patient-Centered Research and Reviews, 2019)
In providing care for adolescents, maintaining confidentiality should be considered a human right and an evidence-based component of quality care. Unfortunately, complexities in the U.S. legal and health care systems have created a setting in which confidential care is inaccessible to many adolescent patients. Federal laws provide a minimum standard for confidentiality protections, but variations in state legislation relating to minor consent, special health care services, and confidentiality exemptions create large variability in adolescent confidentiality rights across the country. In certain contexts, such as consensual sexual activity, legal provisions may not align with professional ethical standards in adolescent care. In addition, contemporary clinical and administrative issues related to the electronic health record and health care financing also threaten to breach confidentiality. Although further research is necessary, providers and institutions are already well positioned to broaden protections by implementing best practices in training and education, workflow, and medical records related to adolescent confidentiality.